2018
DOI: 10.1016/j.bbadis.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 2 cooperating with Fyn promotes kidney fibroblast activation and fibrosis via STAT3 and AKT

Abstract: Sphingosine kinases (Sphks) are the rate-limiting enzymes in the conversion of sphingosine to biologically active sphingosine-1-phosphate. The present study aimed to determine the role of Sphk2 and its downstream targets in renal fibroblast activation and interstitial fibrosis. In the kidney interstitium of patients with renal fibrosis, Sphk2-expressing cells (mainly interstitial fibroblasts) were significantly elevated and highly correlated with disease progression in patients. In a murine model of renal inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…FYN (an SRK member) has been reported to interact with STAT3. Researchers have also reported that the FYN-STAT3 axis is crucial in renal and pulmonary fibrosis [ [26] , [27] , [28] ]. The current study confirmed that FYN influenced phospho-STAT3 expression using knockdown and overexpression models.…”
Section: Discussionmentioning
confidence: 99%
“…FYN (an SRK member) has been reported to interact with STAT3. Researchers have also reported that the FYN-STAT3 axis is crucial in renal and pulmonary fibrosis [ [26] , [27] , [28] ]. The current study confirmed that FYN influenced phospho-STAT3 expression using knockdown and overexpression models.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we and others have shown that SK2 serves as an attractive novel target to treat renal fibrosis. By using SK2-deficient mice, tubulointerstitial fibrosis, induced by either ureter ligation (UUO) 12,13 or folic acid administration 14 , was reduced as compared to wildtype mice. However, no consensus about the underlying mechanism can be drawn from these different studies.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have started to investigate the role of SK2 in renal pathologies, and have shown that SK2 is expressed in tubuli and in the renal interstitium 12,13 . Our group demonstrated that SK2 protein and activity is strongly upregulated in fibrotic renal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with our findings, recently published data suggest that Sphk2 and/or S1P are associated with negative health outcomes. Sphk2 has been shown to promote kidney fibrosis via phosphorylation of Fyn to activate STAT3 and AKT, which could not be rescued by addition of extracellular S1P [42]. Increased S1P levels have been recently associated with type 2 diabetes and obesity [21,22].…”
Section: Discussionmentioning
confidence: 99%